Construção de sentidos da sobrecarga no trabalho por professores do magistério superior: o tema da saúde via atividade linguageira - Sartori, Danieli Ghedin (2017)
The present thesis proposes to question, explore and expose the importance of the sense of the overload of teaching in the health causing sickness. The research was carried out in the university teaching of a Federal University campus in the southwest region of the State of Paraná. For this purpose, a general objective was established to verify aspects related to the work overload, which is directly related to the health of the professionals, by considering the discourse of two professors of the mentioned university. Specific objectives were settled to verify how professors experience work overload and its relation to health, as well as to identify the sense of work overload revealed in the discourse of the university professors and, finally, to analyze how this overloading is signified and re-signified during self-checking sessions. The theory related to the professor’s labor was based on Marx (2014), Castel (2005), Sennet (2007), Clot (2011), Amigues (2004), Nóvoa (1999), Codo (2006), Esteve (1999) and Lemos (2005). For the discussion of the overload, Wisner (1994), Ferreira and Freire (2016) and Lemos (2005); for the discussion of health, Canguilhem (2015), Morschel (2014) and Clot (2010); to deal with work psychopathology, Lima (2005), Le Guillant (2006) and Bendassolli (2011) and for language and sense, Bakhtin (2011, 2014), Lima (2015), Brait (2002), Vigotski (2009), Tezza (2007) and Amorim (2014). The methodology used in the production of the data was that of self-confrontation, which is a methodology adopted in the clinical activity. The dissertation involves the refinement of transcripts of self-confronts with the visualization of the videos, selection of passages that refer to the sense of overload and health and analysis. The study evidenced the possibility proposals for action regarding the health of professors in the work environment. The results also point to a constant and joint change, integrating professors and other professionals concerned about health, through dialogical relationships, which allow the construction of sense and power of action.